Effects of Standardized Ileal Digestible Lysine Level on Growth Performance in 120 to 170 lb DNA Finishing Pigs - Rafe Q. Royall; Robert D. Goodband; Mike D. Tokach; Joel M DeRouchey; Jordan T. Gebhardt; Jason C. Woodworth (Kansas Agricultural Experiment Station Research Reports, 2021)
The objective of this study was to estimate the SID Lys requirement for growth and feed efficiency of 120- to 170-lb finishing pigs. A total of 700 barrows and gilts (600 × 241, DNA; initial BW of 117.2 ± 1.89 lb) were used in two separate studies, each lasting 21-d. Pens of pigs were blocked by BW and randomly allotted to 1 of 6 dietary treatments with 8 to 10 pigs per pen in a randomized complete block design. A similar number of barrows and gilts were placed in each pen. Dietary treatments were corn-soybean meal-based and formulated to 0.65, 0.72, 0.79, 0.86, 0.93, and 1.00% SID Lys, with 12 replications per treatment. Increasing SID Lys increased (linear,P<0.001) ADG, with pigs fed 1.00% SID Lys having the greatest final BW. In addition, increasing SID Lys decreased (quadratic,P= 0.004) ADFI. Feed efficiency improved, while Lys intake/d, and Lys intake/kg of gain increased (quadratic,P<0.005), with increasing SID Lys. At both high and low ingredient and pig prices, feed cost/pig increased (quadratic,P<0.05) as SID Lys increased, while feed cost/lb of gain decreased (quadratic,P<0.001), with pigs fed 0.79% SID Lys having the lowest feed cost/lb of gain. At high and low feed prices, increasing SID Lys increased (linear,P<0.002) IOFC. A linear model resulted in the best fit for ADG and predicted that the maximum ADG response was beyond 1.00% SID Lys. For F/G, the quadratic polynomial model predicted a requirement of 0.97% SID Lys. At high ingredient and pig prices, the broken-line linear model to maximize IOFC predicted that there was no further significant improvement to IOFC past 0.76% SID Lys. Meanwhile, at low ingredient and pig prices the quadratic polynomial model predicted a requirement of 0.91% SID Lys to maximize IOFC, however, a similar fitting linear model predicted maximum IOFC response at greater than 1.00% SID Lys. In summary, the optimal SID Lys level for 120- to 170-lb finishing pigs depends upon the response criteria, with growth performance optimized at or greater than 0.97% SID Lys and IOFC maximized between 0.76 to 0.91% SID Lys.
Keywords: finishing pig; lysine; requirement